Improving Work Attitudes And Assistive Devices Can Reduce Subjective Complaints And Increase The Productivity Of Weavers - Sudarmanto, I Gede; Purna, I Nyoman; Jirna, I Nyoman; Mastra, I Nyoman; Rusminingsih, Ni Ketut; Sudiadnyana, I Wayan (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Gringsing weaving products is a part of handicraft or home industry. They are still confessed at present and produced by simple technology with hand in hand. This activity as a business of income from the most of women in Tenganan Pegringsingan Village of Manggis Sub District, Karangasem Regency. A work attitude with no planned well and they do not use a tool instruments for helping then working correctly, it is caused a subjective complaints of the workers so the production is not maximally and will cause the productivity of the workers come down. Woven products workers is required a carefulness and neatness of the workers, with long sitting posture on the flour covered by something material. It is not aware of this problem in to the anatomy and physiology of the workers and they will have a lot of complaint, sick, or pain on their next, hand, low back, anus, thigh, eyes. It is caused static work load frequently, so that they will be to come a decrease activity and low motivations, it’is activity and the work is not done efficient and effective. The variable that is measured in this study is decrease workload, subjective complaint, work efficiency (long work), and work productivity. The research has been studied to the sixteen weaving workers that were chosen without rules with treatment by subject program with cross over design, its analyses unit considering group variance. It has been intervened by work attitude with supporting tool for instant ‘peliper, tingklik, por (supported by sponge), barble, and using eyes glasses and group workers. This study is analyzed by t-paired, and there is a significant work load reduction (p<0.005), which is the pulse of the workers come down from 89,62 beats per minutes to be 82,56 beats per minutes (±5,60) in the same of the light work load category. The subjective complaints of the work load come down showed significant value (p<0.005) that is from Nordic Body Map score 56,92 (16.14) to be 28.86 (7.32). By the efficient work 7 hours a day with support tools, it is to be come the productivity increase (0,34%) and work productivity (7,9%) significantly (p<0.005).